Intergenerational Learning and Its Impact on the Improvement of Educational Processes - Juan Manuel Trujillo-Torres; Inmaculada Aznar-Díaz; María Pilar Cáceres-Reche; Trinidad Mentado-Labao; Aleix Barrera-Corominas (MDPI AG, 2023)
The promotion of intergenerational dialogue is postulated as one of the most frequently used strategies to promote meaningful learning. The objective is to analyze the impact of intergenerational dynamics on the learning process. To this end, this work is based on the methodology of a systematic review following the PRISMA method through the establishment of inclusion and exclusion criteria and analysis of their suitability. The priority indicator was to collect empirical experiences in the WOS and Scopus databases that implemented strategies on intergenerational learning and promoted improvements in learning, obtaining a total of 14 documents to be analyzed. The results of the review reaffirm the effectiveness of promoting dynamics of this type, observing positive outcomes in different sets of samples in six main areas: (1) attitudes, well-being, and happiness; (2) integration of vulnerable groups; (3) improvement of family relationships; (4) promotion of social and human values; (5) prevention of diseases and increased knowledge about health; and (6) combating the generational digital divide. There are also weaknesses associated with these experiences, such as the strong involvement required by the participants or the initial prejudices that exist between one generation and another.